Creating healthy remote store food environments: use of the Store Scout App in practice - Amanda Hill; Meaghan Christian; Gina Absalom; Brianna Sanderson; Hannah Downes; Sheida Navidi; Anna Murison; Emma McMahon; Grace Dwyer; Julie Brimblecombe (BMC Public Health)
Abstract Background The retail food environment influences food options and purchasing behaviour. Nutrition professionals can support food retailers to create health-enabling food environments. The Store Scout App (Store Scout) is a decision-support tool designed to facilitate this - it rapidly assesses health-enabling store practice and provides real-time feedback to retailers. This research aimed to assess the use of Store Scout by nutrition professionals in their practice to support retailers further their adoption of best-practice for community health improvement. Methods Store owners of 30 stores in Aboriginal remote communities of Central Australia were invited to participate. Nutrition professionals servicing these stores received online training in creating healthy remote stores and access to Store Scout. Store appraisals using Store Scout were conducted from March 2021-August 2022. Practice change was assessed quantitatively using practice scores out of 100 generated by Store Scout for seven food categories and overall (baseline and follow-up). Usability was assessed qualitatively using semi-structured interviews with the nutrition professionals based on the Modified System Usability Scale. Thematic analysis was performed using Gale’s framework method for qualitative data analysis. Results Fourteen of sixteen consented stores had appraisals completed at baseline, and 10 of the 14 stores at follow-up. Average overall practice scores increased from 60% (95%CI 53,67) at baseline to 64% (95%CI 56,73) at follow-up. Nutrition professionals (n = 4) found Store Scout quick and easy-to-use. The App helped facilitate effective collaboration with remote retailers. The ability to provide instant feedback and actionable evidence-based suggestions was an asset. Key recommendations to improve usability were identified. Conclusions Store Scout is useful in practice to enhance engagement between nutrition professionals and retailers and shows potential to support adoption of healthy food retail best-practice and monitoring for continuous improvement. Its potential to support healthy food retailing in non-remote settings warrants investigation.